Common contact sensitizers in the Czech Republic. Patch test results in 12,058 patients with suspected contact dermatitis - Machovcová, Alena; Dastychová, Eliška; Košťálová, Dagmar; Vojtěchovská, A; Reslová, Jaroslava; Šmejkalová, Dana; Vaněčková, Jaroslava; Vocilková, Andrea (Contact dermatitis, 2005)
The patch test results of 12 058 patients (4416 male and 7642 female) referred to 9 clinics in the Czech Republic between January 1997 and December 2001 were evaluated. Patients were tested with the same series of allergens by using the standardized patch testing method. The current standard tool for diagnosing allergic contact dermatitis (ACD) in the Czech Republic is the Trolab test panel (Hermal, Reinbeck, Germany) which consists of 23 allergens. Only a few data exists on ACD in the Czech Republic. All patients were tested with the 23 allergen European standard series. Of these patients, 7661 (63.5%) had 1 or more positive reactions. On average, there were 2.8 positive reactions per patient. ACD, according to clinical relevance, was diagnosed in 5339 (69.7%) of these patients. The most frequent allergens were metals (22.9%), especially nickel sulfate (13.8%), and followed by Myroxylon pereirae resin (balsam of Peru) (7.3%), fragrance mix (5.8%), formaldehyde (4.2%) and lanolin alcohol (3.0%). Our results were compared with results from other countries. We conclude that the European standard series is suitable for detection of ACD in the Czech Republic.
Keywords: dospělí; Female; dítě; Adult; Allergens; ženské pohlaví; Adolescent; lidé; Dermatitis, Allergic Contact; alergická kontaktní dermatitida; Patch Tests; Male; Aged; Czech Republic; náplasťové testy; Česká republika; alergeny; lidé středního věku; Child; senioři; mužské pohlaví; Middle Aged; mladiství; Humans